HUBUNGAN DAYA LEDAK OTO TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRI KELAS IV SDN 018 SUNGAI KERANJI KECAMATAN SINGINGI - Sugiyarto '; Saripin '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is some of female studnets of SDN 018 Sungai Keranji are the result of squat style long jump that does not reach the target. This is presumably because one of the factors that condition explosive power leg muscle. So, the researchers wanted to prove by means research. Type of research is correlational research that collected two variables: the variables x and y. As the variable x is the explosive power leg muscle of female students class IV of SDN 018 Sungai Keranji District of Singingi and variable y is the squat style long jump result female students class IV SDN 018 Sungai Keranji District of Singingi. The sample in this study specifically taking a class IV female students SDN 018 Sungai Keranji District of Singingi totaling 25 people. Data obtained from the results of tests measuring the standing broad jump and squat style long jump. From the results of calculations found the value of r count is 0.415 with the value rtabel = 0.396, it means rcount = 0.415> rtabel = 0.396 and it can be said that there is a relationship between the explosive power leg muscle with the squat style long jump results female students class IV SDN 018 Sungai Keranji district of Singingi. Criteria for hypothesis testing Ho accepted if tcount smaller than ttable while the calculation results show that t = 2.19> table = 1.714, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that "there is a corelation between the explosive power leg muscle with the squat style long jump rseults female students class IV SDN 018 Sungai Keranji District of Singingi. "accepted.Keywords : Explosive Power, Leg Muscle, Squat Style, Long Jump2